Effective low-dose Anlotinib induces long-term tumor vascular normalization and improves anti-PD-1 therapy - Fan, Peng; Qiang, Huiping; Liu, Zhenhua; Zhao, Qi; Wang, Ying; Liu, Tingkun; Wang, Xuan; Chu, Tianqing; Huang, Yuhui; Xu, Wei; Qin, Songbing (Frontiers in Immunology, 2022)
Anlotinib is a new multitarget tyrosine kinase inhibitor for tumor angiogenesis and its monotherapy exhibits decent clinical efficacy. However, how to combine Anlotinib and immune checkpoint therapy to achieve optimal antitumor effects while limiting side effects remains unclear. In this study, we found that effective low dose Anlotinib was sufficient to inhibit tumor growth while reduced side effects compared with high dose. Effective low dose Anlotinib treatments induced durable tumor vascular normalization and improved anti-PD-1 therapy in both short- and long-term treatment regimens. Mechanistically, the combination therapy increased the proportions of intra-tumoral CD4+ T, CD8+ T and NK cells. Anlotinib-associated anti-tumor effects were independent on interferon γ, however, the combination therapy required CD8+ T cells to suppress tumor growth. Together, these results suggest that the combination of effective low dose Anlotinib and PD-1 blockade induces durable anti-tumor effects with less side effects. Our findings indicate that anti-angiogenic treatments combined with immune checkpoint therapy at effective low dose, rather than tolerant high dose, would be more efficacious and safer.